A comparison of the contributions of Japanese and English-Canadian parents to their children's education. - Fanjoy, Andrea S. (University of Ottawa (Canada), 1999)
Education reforms throughout much of Canada reflect growing awareness of the role parents can play in an effective system. Though the relationship between parent involvement and student achievement is well established, how much time and money parents contribute to their children's education was largely unknown. To determine this for a sample of English-Canadian parents and to learn by comparison with a Japanese sample, 48 English-Canadian parents and 115 Japanese parents of children in grade 5 completed a survey on their contributions of time and money. They were also asked about their perceptions of the roles of home and school, aspirations for their children and motivations for spending their time and money in this way. While no significant differences were found in the total amount of money parents spent, there were many significant differences in how they spent it. Regarding time, English-Canadian parents spent more on almost every measure. Contrary to expectations, these findings raise many questions about previous research and prevailing attitudes regarding Japanese and English-Canadian parent involvement in education.
Keywords: Education, Elementary.